PERBANDINGAN BEBERAPA METODE DIAGNOSIS ANEMIA DEFISIENSI BESI: usaha mencari cara diagnosis yang tepat untuk penggunaan klinik - Suega, Ketu; Bakta, I Made; Adnyan, Losen; Darmayuda, Tjok (journal of internal medicine, 2012)
Iron deficiency anemia (IDA) is the most widespread public health problems. In 1989 WHO report more than one third of worlds population suffered from anemia and half of them with iron deficiency anemia. Iron deficiency anemia can cause reduced work capacity in adults and impact motor and metal devolepment in children and adolescents. It also can increase risk of infection, mother mortality rate, affects cognition in adulescents girls and causes fatique in adult women. IDA may affect visual and auditory functioning and is weakly associated with poor cognitive development in children. The diagnosis of IDA requires proper clinical manifestation, laboratory evidence and also others diagnostic test that support iron deficiency. There are some diagnostic tests frequently use in clinical practice to diagnose IDA, such as the morphology of erytrosite, examination of serum iron and total iron binding capacity, examination of feritin serum, and bone marrow staining. Knowing the best of diagnostic methods can use in clinical practice and also knowing the profile of IDA, can leads into better management of IDA in population. A diagnostic test was done in order to know the sensitivity and spesifity of erytrosite index, serum iron, TIBC, and feritin serum in dignostic IDA. The study was done at Internal Departement, Sanglah Hospital for 6 months, start from March 2003 until October 2003. The result is Feritin has the best sensitivity (90.6%) and specificity (90.6%) , with cut off point 35.4 µg/l. MCH as erytrosite index has sensitivity (84.4%) and specificity (75%) to diagnose IDA, the cut off point is 21.8 pg . Sensitivity and specificity of TIBC is 81.3% and 83.8% with cutt off point 282 µg/l. Sensitivity and specificity saturation of transferin is 84.4% and 79.7% with cutt off point 6%. Serum iron has sensitivity 75.0% and specificity 68.7% with cut off point 17 µg/l.
Keywords: iron deficiency anemia, diagnostic test